New Gomphoneis Cleve (Bacillariophyceae: Gomphonemataceae) species from Xinjiang Province, China - You, Qingmin; Kociolek, John Patrick; Wang, Quanxi (Phytotaxa, 2013)
Eight new species of the diatom genus Gomphoneis Cleve from Xinjiang Province of northwest China are described. Observations were made using light and scanning electron microscopy, documenting the morphological diversity of the taxa, all of which are part of the G. elegans lineage, and lack isolated stigmoids. Five of the new species (Gomphoneis pseudosubtiloides, G. xinjiangiana, G. basiorobusta, G. stoermeri and G. distorta) have porelli in the apical pore fields organized into two rows, similar to the organization of the striae areolae. Three species (G. subtiloides, G. qii and G. rostratoides) have porelli of similar size, shape and organization to the areolae, supporting the interpretation that the apical pore fields in this group are condensed striae. The species from Xinjiang Province appear morphologically similar to taxa from the Balkans of Europe, and may be part of a wide continuum of distribution between that region and western North America. This is only the second report on Gomphoneis from Xinjiang Province. A number of taxa similar to the new species described herein, and related to Gomphoneis olivacea, are also considered. As a consequence, the total number of Gomphoneis taxa from China is greater than previously recognized.